Association of household fuel with acute respiratory infection (ARI) under-five years children in Bangladesh - Islam, Md. Aminul; Hasan, Mohammad Nayeem; Ahammed, Tanvir; Anjum, Aniqua; Majumder, Ananya; Siddiqui, M. Noor-E-Alam; Mukharjee, Sanjoy Kumar; Sultana, Khandokar Fahmida; Sultana, Sabrin; Jakariya, Md.; Bhattacharya, Prosun; Sarkodie, Samuel Asumadu; et al. (Frontiers in Public Health, 2022)
In developing countries, acute respiratory infections (ARIs) cause significant number of children deaths around the worldwide. According to Bangladesh Demographic and Health Survey (BDHS), about 25% children death under five years caused by acute respiratory infection (ARI) in Bangladesh every year. Low-income families frequently rely on wood, coal, and animal excrement for cooking. However, it's unclear whether using alternative fuels offers a health benefit over solid fuels. To clear this doubt, we conducted a study to investigate the effects of fuel usage on ARI in children. In this study, we used the latest Bangladesh Demographic & Health Survey (BDHS) 2017-18 data created by Government of Bangladesh (GoB) (https://dhsprogram.com/data/available-datasets.cfm), and estimated the effects of fuel use on ARI by constructing logistic regression models. The risk factors for ARI due to fuel use were assessed using a multivariable logistic regression model. From the analysis, we found the crude (the only type of fuel in the model) odds ratio (OR) for ARI was 1.693 [95% confidence interval (CI): 1.058-2.709]. This suggests that children in families using contaminated fuels were 69.3% more likely than children in households using clean fuels to experience an ARI episode. After adjusting for cooking fuel, type of roof material, child's age (months), and sex of the child, the effect of solid fuels was also more acute as the adjusted odds ratio (AOR) for ARI was 1.692 (95% CI: 1.053-2.718). This implies that when compared to the effect of clean fuel, an ARI occurrence is 69.2% more likely. This study finding found a statistical significant association between solid fuels consumption and the occurrence of ARI in children in households. The correlation between indoor air pollution and clinical parameters of acute respiratory illness requires investigations. The study findings will also help other researchers and policymakers to take comprehensive actions by considering ARI as a risk factor as well as enhance for taking proper steps for solving this issue.